Digitalization and Energy Transition for Sustainable Development in North Africa: New Evidence from the CS-ARDL Approach - Amayed, Yasser (International Journal of Energy Economics and Policy, 2025)
This paper examines the impact of digitalization and energy transition on economic growth in North African countries from a sustainable development perspective. Using the CS-ARDL model, we distinguish between short-run dynamic adjustments and long-run structural relationships that reflect the combined influence of fixed capital investment, renewable and non-renewable energy consumption, and the diffusion of information and communication technologies (ICT). Our results suggest that in the short run, productive investment and fossil fuel dependence stimulate economic activity. In the long run, the gradual integration of renewable energy and the improvement of digital infrastructure promote more inclusive and resilient growth in line with the Sustainable Development Goals. The analysis also reveals significant structural and regional disparities, underscoring the need for differentiated and coordinated public policies to optimize the synergy between digitalization and energy transition.